The associations between attachment, sexual motives, and sexual desire - Peng, Yanqun (Kansas State University, 2019)
Studying sex is relatively new in Chinese culture and little is known about Chinese couples’ sexuality (Cheung et al., 2008). There is insufficient sex education in China and people with sexual dysfunctions are hesitated to seek help for sexual issues due to cultural norms (So & Cheung, 2005). Additionally, many people attribute their sexual dysfunction or problems to somatopsychic origins and use folk medicines to treat problems (So & Cheung, 2005) and few studies have focused on the mechanisms related to sexual desire for Chinese men and women (Woo et al., 2012). Our goal, therefore, is to understand psychological and relational mechanisms associated with sexual desire for Chinese adults and offer some culturally sensitive clinical suggestions to improve sexual desire treatment for Chinese couples. We utilized 398 individuals with 166 women (age 18-50) and 232 men (age 18-70). The current study tested the direct relationships between attachment style (i.e., anxious and avoidant) and sexual desire (i.e., partner-focused and general sexual desire) and the indirect relationships via approach and avoidance sexual motivation for women and men. We also tested whether women and men are different in these associations. We found the following findings. First, attachment anxiety was negatively linked with approach sexual motivation for both groups. However, the negative link between attachment anxiety and approach sexual motivation was stronger for men (b = -.405, p < .001, β = -.353) than woman (b = -.312, p = .020, β = -.280). Second, attachment anxiety was directly and negatively linked with partner-focused sexual desire for both groups. However, the link between attachment anxiety and partner-focused sexual desire was stronger for women (b = -.272, < .001, β = -.367) than for men (b = -.175, p < .001, β = -.302). Third, approach sexual motivation had significant and positive links with partner-focused sexual desire (b=.196, p < .001) and general sexual desire (b=.111, p < .001) for both groups equally. Fourth, attachment avoidance was positively linked with avoidance sexual motivation for both men and women (b=.292, p < .001), indicating that higher levels of attachment avoidance are related to higher levels of avoidance sexual motivation. Fifth, avoidance sexual motivation was related to partner-focused sexual desire (b = -.138, p = .005, β = -.193) and general sexual desire (b = -.088, p = .058, β = -.158) for women, but not men. These results point to the importance of coping with attachment anxiety. Second, these results provide important initial evidence that approach sexual motivation is an important pathway or mediator through which attachment anxiety is associated with partner-focused and general sexual desire. Third, even though avoidance behaviors and motivations are more acceptable and common in Chinese populations, it was negatively associated with women’s sexual desire. Avoidance behaviors and avoidance sexual motivations, therefore, are maladaptive at least for Chinese women in this context.
Keywords: Attachment; Approach sexual motives; Sexual desire; Avoidance sexual motives; Chinese